2023
DOI: 10.3341/kjo.2022.0125
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Defocus and Myopia Management: A Mini-Review

Abstract: Myopia is the most common refractive error in the world, and its’ prevalence continually increases. The potential pathological and visual complications of progressive myopia have inspired researchers to study the sources of myopia, axial elongation, and explore modalities to arrest progression. Considerable attention has been given over the past few years to the myopia risk factor known as hyperopic peripheral blur, the focus of this review. The primary theories currently believed to be the cause of myopia, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 82 publications
1
9
0
Order By: Relevance
“…The overall defocus distribution of Ok is characterized by the asymmetry of the peripheral retinal defocus between the horizontal and vertical diameters of the retina, with temporal defocus being the most obvious. Erdinest [23] showed that among the defocus of the four 90° wedge-shaped regions centered on the macula,RDV-T was the largest, followed by RDV-N, RDV-S, and RDV-I. The results of the present study were consistent with these ndings.…”
Section: Discussionsupporting
confidence: 90%
“…The overall defocus distribution of Ok is characterized by the asymmetry of the peripheral retinal defocus between the horizontal and vertical diameters of the retina, with temporal defocus being the most obvious. Erdinest [23] showed that among the defocus of the four 90° wedge-shaped regions centered on the macula,RDV-T was the largest, followed by RDV-N, RDV-S, and RDV-I. The results of the present study were consistent with these ndings.…”
Section: Discussionsupporting
confidence: 90%
“… 42 , 43 Furthermore, ChatGPT-3.5 erroneously claimed that Abiliti is an implantable device requiring surgical intervention, while in fact, Abiliti is a contact lens for myopia control available in soft and hard (orthokeratology) forms, without requiring surgical implantation. 44 , 45 The spread of such misinformation by LLM-Chatbots can mislead users, potentially hindering effective myopia management. This further highlights the importance of accurate and reliable information dissemination from LLM-Chatbots.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, myopic individuals exhibit a larger and stiffer ciliary muscle, potentially impacting accommodative function [ 14 ]. The concept of peripheral defocus, characterized by hyperopic defocus in the outer retinal regions, has emerged as a possible contributing element in myopia development [ 15 ]. Nevertheless, the role of peripheral defocus as either a cause or consequence of myopia remains an ongoing debate [ 16 ].…”
Section: Introductionmentioning
confidence: 99%